On Exact Solutions of Some Space-Time Fractional Differential Equations with M-truncated Derivative - Ozkan, Ayten; Ozkan, Erdoan Mehmet; Yildirim, Ozgur (MDPI, 2023)
In this study, the extended G'/G method is used to investigate the space-time fractional Burger-like equation and the space-time-coupled Boussinesq equation with M-truncated derivative, which have an important place in fluid dynamics. This method is efficient and produces soliton solutions. A symbolic computation program called Maple was used to implement the method in a dependable and effective way. There are also a few graphs provided for the solutions. Using the suggested method to solve these equations, we have provided many new exact solutions that are distinct from those previously found. By offering insightful explanations of many nonlinear systems, the study's findings add to the body of literature. The results revealed that the suggested method is a valuable mathematical tool and that using a symbolic computation program makes these tasks simpler, more dependable, and quicker. It is worth noting that it may be used for a wide range of nonlinear evolution problems in mathematical physics. The study's findings may have an influence on how different physical problems are interpreted.
Keywords: the extended G'/G method; Burger-like equation; coupled Boussinesq equation; M-truncated derivative; BOUSSINESQ EQUATION; WAVES; DISPERSION; Mathematics